Decline of Local Democracy: Legal Vacancies, Non-Ideological Coalitions, and the Phenomenon of Single Candidates in Regional Elections in Indonesia - Pratama, Romadhony Putra; Cornelis, Vieta Imelda; Astutik, Sri; Handayati, Nur; Isnawati, Isnawati (Dinasti Research, 2026)
The consolidation of democracy in post-Reform Indonesia is currently facing an